The influence of women on the British Labour Party in the 1920s - Ruhl, Kathrin; Justus Liebig University Giessen (My University, 2004)
Der Artikel untersucht, in wiefern es die weiblichen Mitglieder der britischen Labour Party vermochten, den Diskurs der Partei in den 1920ern mitzubestimmen. Frauen wurden im Jahr 1918 in die Partei aufgenommen und traten dieser im Verlauf der 20er Jahre verstärkt bei. Der erste Teil des Artikels beleuchtet anhand einer Analyse der Parteistrukturen, ob die Parteiorgane, die maßgebliche Entscheidungen treffen konnten, gewillt waren, Frauen an der Macht zu beteiligen. Der Kampf der weiblichen Parteimitglieder um Einflussnahme wird im zweiten Teil des Beitrages durch eine Fallanalyse zur Einführung von Familienbeihilfe vertieft.

This article seeks to explore in how far women members were able to influence the discourse of the British Labour Party in the 1920s. Women were integrated organisationally in 1918 and joined the party in large numbers throughout the 1920s. By providing an examination of the party structures, the first section of this article will discuss whether the decision making bodies of the Labour Party were willing to share power with the women members. The analysis of the struggle of Labour women to influence the party and the shaping of its policies is extended in the second section by a case study of family allowances.
The influence of women on the British Labour Party in the 1920s
Keywords: Frauen und Politik; Labour Party; Familienbeihilfe; women and politics; Labour Party; family allowances; ddc:320